Synthesis of Chiral o-Aminobenzylamines by Stereoselective Addition of Grignard Reagents to N-[(o-Aminophenyl)methylene] sulfinamides - Zhong, Xianqiang; Xiao, Guorong; Zhou, Wei (Synlett, 2021)
Chiral o-aminobenzylamines are synthons for many chiral ligands and catalysts that have been widely used in asymmetric synthesis. Here, we report a highly efficient and stereoselective addition of Grignard reagents to N-[(o-aminophenyl)methylene]sulfinamides to give a range of o-aminosulfinylimines in good yields with good to excellent diastereoselectivities.
Keywords: diamines; aminobenzylamines; sulfinamides; Grignard reagents; stereoselectivity